Application of Mobile Learning to Increase Interest in Learning Science in Class VII Junior High School Students - Chandra Dwi Henita Sari; Zuhdi Ma'aruf; M. Rahmad (Journal of Indonesian Science Teachers, 2023)
This research aimed to determine the increase in students' interest in learning science by studying the concept of material classification and its changes, through mobile learning learning media. The research method uses a pretest-posttest control group design with quantitative data types. Data on students' learning interests was collected through distributing learning interest questionnaires before and after learning using mobile learning media. The research instrument was prepared based on ARCS learning interest aspects (attention, relevance, self-confidence, and satisfaction). Data were analyzed descriptively using a Likert scale and inferentially using the Independent Sample T-Test. The results of the research showed that students' interest in learning had increased in the experimental class with a good category of 83% and a very good 17%. Inferentially, a significant increase in interest in learning was obtained. These results provide the conclusion that the application of mobile learning media has a positive impact on increasing student interest in learning better in learning material classification and its changes in class VII Junior High School.